Grit Akademik Mahasiswa: (Deferensiasi Gender Pada Pembelajaran Online Statistika di Era Revolusi Industri 4.0) - Amalia, Kiki; Syifa, Abdullah (LPPM Institut Pendidikan Nusantara Global, 2024)
This research aims to determine differences in students' academic grit in online statistics courses based on gender. This research was conducted in 2021 on odd semester Islamic Psychology Study Program students. The population is students who have taken statistics and advanced statistics courses in even and odd semesters, totaling 60 students. The sampling technique used is a total sample, where all members of the population are used as sample members. Data was collected using an academic grit measuring tool in which there are 12 statement items. Data were analyzed using an independent difference test (independent t-test). The results of this research are that there are differences in students' academic grit during online statistics lectures based on gender. The research proportion value obtained was 0.006, where this value was smaller than the research significance value (0.05). This difference is a separate note as an effort to relate it to competence in the era of industrial revolution 4.0. Statistical skills are one of the skills that must be possessed in the era of industrial revolution 4.0. This is because with the existence of